Flowering phenology and pollination of ornithophilous species in two habitats of Serra da Bodoquena, Mato Grosso do Sul, Brazil - Faria, Rogério R.(Universidade Federal de Mato Grosso do Sul Laboratório de Ecologia Programa de Pós-Graduação em Ecologia e Conservação); Araújo, Andréa C.(Universidade Federal de Mato Grosso do Sul Departamento de Biologia Laboratório de Ecologia Cidade) (Anais da Academia Brasileira de Ciências, 2010)
The aim of this study is to describe interactions between hummingbirds and ornithophilous species at Serra da Bodoquena in midwest Brazil, with focus on flowering phenology and pollination of these plant species. In two habitats, gallery forest and semi-deciduous forest, data on flowering phenology of ornithophilous species were collected monthly over 14 months. In addition, data on morphology and floral biology, as well as visitor frequency and hummingbird behavior, were recorded. The studied community contained eight ornithophilous plant species and six hummingbird species. The ornithophilous species flowered throughout the year, and the greatest abundance of flowers was at the end of the rainy season and the beginning of the dry one. The herit huingbird Phaethornis pretrei and feales of Thalurania furcata, were the most similar in floral resource use. Acanthaceae is the most representative family of ornithophilous plant species in Serra da Bodoquena and, thus, represents the main food source for hummingbirds. Ruellia angustiflora is especially important because it flowers continuously throughout the year and is a significant food resource for P. pretrei, which is the main visitor for this plant guild. O objetivo deste estudo é descrever as interações entre beijaflores e espécies ornitófilas na Serra da Bodoquena na região Centro-Oeste do Brasil, com foco na fenologia de floração e polinização destas espécies vegetais. Em dois habitats, mata ciliar e floresta semi-decídua, dados de fenologia de floração de espécies ornitófilas foram coletados mensalmente ao longo de 14 meses. Além disso, dados de morfologia e biologia floral bem como a frequência dos visitantes e o comportamento dos beija-flores foram registrados. A comunidade estudada contém oito espécies de plantas ornitófilas e seis espécies de beija-flores. As espécies ornitófilas floresceram todo o ano, e a maior abundância de flores foi no final da estação chuvosa e início da seca. O beija-flor eremita Phaethornis pretrei e a fêmea de Thalurania furcata foram os mais similares no uso dos recursos florais. Acanthaceae é a família mais representativa das espécies vegetais ornitófilas na Serra da Bodoquena e representa a principal fonte de recurso para os beija-flores. Ruellia angustiflora é especialmente importante porque floresce continuamente ao longo do ano e é uma importante fonte de recurso para P. pretrei, que é o principal visitante floral para esta guilda de plantas.